A natural halogenated fluoride adenosine analog 5′‐fluorodeoxy adenosine induced anticolon cancer activity in vivo and in vitro. Issue 10 (22nd July 2022) - Ma, Long; Liu, Taohua; Lu, Yingying; Dong, Yanan; Zhao, Xia; Man, Shuli
Abstract: Adenosine (ADO) and its analogs have been introduced into the anticancer clinical trials, especial for the ADO derivatives with fluoride. The biosynthesis of fluorinase produces a fluorine‐containing ADO analog 5′‐fluorodeoxy adenosine (5′‐FDA). The toxicity and application of 5′‐FDA has not been evaluated, which limits the application of ADO analogs. In order to study its potential mechanism, we carried out the following experiments. In our research, 5′‐FDA displayed good antitumor activity in colon cancer cells and two colon cancer models. As a result, 5′‐FDA concentration‐dependently inhibited the proliferation, migration, and invasion in colon cancer cells through its proapoptosis and cell cycle arrest pathway. Furthermore, 5′‐FDA inhibited the growth of colon cancer and its pulmonary metastasis in CT26 inbred mice without affecting their body weight. It was found that 5′‐FDA remarkably increased the protein levels of Caspase 3 and cleaved‐Caspase 9 and decreased Cyclin A2 and CDK2 via the regulation of p53 signaling pathway, and increased the protein levels of Caspase 8 and cleaved‐Caspase 8 which participated in apoptosis pathway. All in all, 5′‐FDA displayed excellent therapeutic effects on colon cancer and its pulmonary metastasis. We believed that our study provided a theoretical basis for further preclinical research of 5′‐FDA in the treatment of cancer.